Microfluidic synthesis of high-performance violet-to-blue perovskite quantum dots for light-emitting applications - Jing Li; Shuai Zhang; Jiawei Liu; Kezhou Chen; Lele Cao; Chuantong Cheng; Kebin Lin; Tiegen Liu; Lili Hou (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

A plant-free push–pull system using sustained-release electrospun micro-/nanofibers for insect behavioral manipulation - Chenglong Cui; Xiwei Xia; Zhimin Wang; Ertao Li; Huanhuan Dong; Jiaan Shen; Yujun Sun; Yu Peng; Kebin Li; Jiao Yin (Journal of Pest Science, 2026)

Transferable prediction of TBM long-distance tunneling construction duration considering uncertainties in surrounding rock distribution and the evolution of tunneling efficiency - Jianming Zhang; Kebin Shi; Peixuan Lin; Lei Li; Qiyong Mao; Haibo Jiang; Xinjun Yan; Jingwei Gong (Tunnelling and Underground Space Technology, 2026)

Atmospheric Ultrafine Particles: Emerging Frontiers in Air Quality, Health Effects and Climate Change - Kebin He; Lidia Morawska; Guangjie Zheng; Xiaoxiao Li (ENGINEERING Environment, 2026)

Fine-scale mangrove species monitoring and ecological threshold assessment for coastal management in Quanzhou Bay, China - Siming Chen; Fei Chen; Longhui Niu; Zhong Deng; Kebin Wu; Wenbin Li (Environmental Monitoring and Assessment, 2026)

Transforming steel slag into a soil-like matrix via CO2 sequestration: A strategy for simultaneous waste valorization and carbon emission reduction - Xin Xie; Chen Li; Zhiyuan Ma; Ludan Zhang; Qun Zhao; Jie Li; Senlin Tian; Kebin He (Journal of Environmental Management, 2026)

Emission-trend-constrained quality assessment model for remote sensing data of vehicle NO emissions - Junchao Zhao; Li Peng; Guanlin Zhu; Xinyue Zhao; Zhaofeng Lv; Zhenyu Luo; Zhining Zhang; Xiaohu Wang; Jin Liu; Yingzhi Zhang; Huan Liu; Kebin He (Journal of Hazardous Materials, 2026)

Multi-scale Characterization of Pore Structure Damage in Limestone Grottoes Under the Coupling Effect of Salt Freeze–Thaw - Zhiliu Wang; Mengxin Hu; Jiabao Tang; Yulong Wang; Xinming Li; Song Yin; Kebin Ren; Chaolong Ma (Rock Mechanics and Rock Engineering, 2026)

Cross-media transfer footprint control for sustainable environment management – a perspective from wastewater treatment - Yujun Huang; Yipeng Wu; Xipeng Yu; Miao Li; Kebin He; Shuming Liu (Water Research, 2026)

Integrated UV-protective, water-resistant, and biodegradable core-shell micro/nanofiber mats enabling controlled repellent delivery for sustained pest management - Ertao Li; Chenglong Cui; Wenjie Shangguan; Yafei Qu; Zhimin Wang; Kebin Li; Jiao Yin (Chemical Engineering Journal, 2026)

Environmental catalytic city: New engine for air pollution control - Jinzhu Ma; Biwu Chu; Xiaotong Li; Huihui Wang; Qingxin Ma; Guangzhi He; Qian Liu; Shuxiao Wang; Kebin He; Jincai Zhao; Hong He (Journal of Environmental Sciences, 2025)

Host Egg Preference and Density-Dependent Parasitism of Telenomus remus in Spodoptera litura and Spodoptera frugiperda Eggs - Ibrahim Osman; Zhimin Wang; Ertao Li; Honglin Feng; Jiao Yin; Gemei Liang; Zhengling Liu; Dekai Ning; Kebin Li; Yonghui Xie (Neotropical Entomology, 2025)

Rational design of core-shell polyvinylpyrrolidone (PVP)-MIL-101(Fe)@CoZn-ZIF nanocomposites for peroxymonosulfate activation toward 4-nitrophenol degradation - Mei Dong; Qiguang Cao; Song Li; Kebin Li (Journal of Water Process Engineering, 2025)

Exploring the association between air pollution and urogenital congenital anomalies: a global ecological analysis - Kebin Chen; Hanjun Liu; Tingting Wang; Manjun Luo; Xiaorui Ruan; Mengting Sun; Ziye Li; Jianhui Wei; Jiabi Qin (Environmental Pollution, 2025)

Polysaccharide gel beads co-loaded with yeast and insecticide for sustainable and targeted control of subterranean pests via attract-and-kill strategy - Chenglong Cui; Zhimin Wang; Ertao Li; Wenjie Shangguan; Xiaohu Wu; Jiao Yin; Kebin Li (Chemical Engineering Journal, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Strategic approach to reduce environmental damage by CO2 and air pollution based on Energy-Material-Emission Nexus: Insights from Beijing - Daiwei Ouyang; Qingru Wu; Shuxiao Wang; Kaiyun Liu; Shengyue Li; Yao Li; Xinyun Chen; Kun Wang; Wenhao Wu; Zhaoxin Dong; Yueqi Jiang; Yanning Zhang; et al. (Resources, Conservation and Recycling, 2025)

Constitutive Behavior of Silt Under Dry–Wet Cycles and Nonlinear Strength Effects - Xinming Li; Jinming Geng; Kebin Ren; Song Yin; Yuzhou Sun; Yunzhi Tan (Geotechnical and Geological Engineering, 2025)

Features of particle-phase PAHs from traffic emissions using tunnel measurement and urban roadside observation in China - Fei Gao; Zhitao Cai; Zhenyu Luo; Junchao Zhao; Songxin Zheng; Li Wang; Bi Chen; Kebin He; Huan Liu (Environmental Pollution, 2025)

Visible-light-assisted peroxymonosulfate activation using MIL-88A(Fe)/BiOI heterojunction composite to drive charge transport for eliminating acid red 18 - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hongna Zhang; Nannan Zhong; Hai-Ying Jiang (Journal of Environmental Chemical Engineering, 2024)

Upcycling of polyethylene/polypropylene mixtures promoted by well-controlled multiblock olefin copolymers - Yuze Kang; Hanlin Wang; Fanmao Meng; Shangtao Chen; Bin Du; Zihao Jiang; Jiajia Wu; Kebin Zhang; Huan Gao; Li Pan; Yuesheng Li (Chemical Engineering Journal, 2024)

2,3-pyridinedicarboxylic acid-modified MIL-88A(Fe) for enhanced peroxymonosulfate activation to degrade organic contaminants - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hai-Ying Jiang (Journal of Water Process Engineering, 2024)

The Role of Histone H2B Acetylation Modification in Aluminum-Induced Cognitive Dysfunction - Jie Gao; Wei Liu; Jing Pei; Jing Li; Niping Hao; Shuo Yang; Xiaoming Yang; Danfeng Zou; Kebin Xu; Lifeng Zhang (Biological Trace Element Research, 2024)

Spatiotemporal carbon footprint and associated costs of wind power toward China's carbon neutrality - Ziwen Ruan; Xi Lu; Zihua Yin; Shawn C. Mobley; Chongyu Zhang; Jiaxing Wang; Yan Li; Zhaoyang Kong; Guang Shi; Dan Chen; Kebin He (Resources, Conservation and Recycling, 2024)

Aurantio-obtusin Alleviates Dry Eye Disease by Targeting NF-κB/NLRP3 Signaling in Rodent Models - Dan Zhu; Na Zheng; Kebin Deng; Liangchang Li (Biochemical Genetics, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

Changes in Mental Health and EEG Biomarkers of Undergraduates Under Different Patterns of Mindfulness - Miaoling Luo; Quan Gan; Ziyang Huang; Yunxiong Jiang; Kebin Li; Minxiang Wu; Dongxiao Yang; Heng Shao; Yanmei Chen; Yu Fu; Zhuangfei Chen (Brain Topography, 2024)
The effects of short-term mindfulness are associated with the different patterns (autonomic, audio guided, or experienced and certified mindfulness instructor guided mindfulness). However, robust evidence for reported the impacts of different patterns of mindfulness on mental health and EEG biomarkers of undergraduates is currently lacking. Therefore, we aimed to test the hypotheses that mindfulness training for undergraduates would improve mental health, and increase alpha power over frontal region and theta power over midline region at the single electrode level. We also describe the distinction among frequency bands patterns in different sites of frontal and midline regions. 70 participants were enrolled and assigned to either 5-day mindfulness or a waiting list group. Subjective questionnaires measured mental health and other psychological indicators, and brain activity was recorded during various EEG tasks before and after the intervention. The 5-day mindfulness training improved trait mindfulness, especially observing (p = 0.001, d = 0.96) and nonreactivity (p = 0.03, d = 0.56), sleep quality (p = 0.001, d = 0.91), and social support (p = 0.001, d = 0.95) while not in affect. Meanwhile, the expected increase in the alpha power of frontal sites (p < 0.017, d > 0.84) at the single electrode level was confirmed by the current data rather than the theta. Interestingly, the alteration of low-beta power over the single electrode of the midline (p < 0.05, d > 0.71) was difference between groups. Short-term mindfulness improves practitioners’ mental health, and the potentially electrophysiological biomarkers of mindfulness on neuron oscillations were alpha activity over frontal sites and low-beta activity over midline sites.

Covalent organic framework-based immunosensor to detect plasma Latexin reveals novel biomarker for coronary artery diseases - Xiuzhen Li; Huaibin Wan; Yang Tian; Jingzhu Wang; Shaohua Xu; Kebin Huang; Hong Liang; Ming Chen (Analytica Chimica Acta, 2023)

Navigating the future: China’s photovoltaic roadmap challenges - Moisés Gómez; Guochang Xu; Yan Li; Jinhui Li; Xi Lu; Kebin He; Xianlai Zeng (Science Bulletin, 2023)

A real-time NO emission inventory from heavy-duty vehicles based on on-board diagnostics big data with acceptable quality in China - Zhaofeng Lv; Yingzhi Zhang; Zhe Ji; Fanyuan Deng; Mengshuang Shi; Qiwei Li; Miao He; Lin Xiao; Yingnan Huang; Huan Liu; Kebin He (Journal of Cleaner Production, 2023)

Comparative genomics studies on the stk gene family in vertebrates: From the bighead carp (Hypophthalmichthys nobilis) genome - Yang Mao; Defeng Li; Rongrong Chen; Caifeng Ma; Junzhi Xiong; Kebin Zhang (Fish & Shellfish Immunology, 2023)

Classification and sources of extremely severe sandstorms mixed with haze pollution in Beijing - Tianyi Liu; Fengkui Duan; Yongliang Ma; Tao Ma; Qinqin Zhang; Yunzhi Xu; Fan Li; Tao Huang; Takashi Kimoto; Qiang Zhang; Kebin He (Environmental Pollution, 2023)

A review and evaluation of nonroad diesel mobile machinery emission control in China - Pengju Bie; Liang Ji; Huanxing Cui; Gang Li; Shunli Liu; Ying Yuan; Kebin He; Huan Liu (Journal of Environmental Sciences, 2023)

Octopamine modulates insect mating and Oviposition - Dandan Liu; Xinxin Zhang; Fang Chiqin; Innocent Nyamwasa; Yazhong Cao; Jiao Yin; Shuai Zhang; Honglin Feng; Kebin Li (Journal of Chemical Ecology, 2022)

Experimental Research on Steel slag Stabilized Soil and its Application in Subgrade Engineering - Shige Wang; Xinming Li; Kebin Ren; Chenhui Liu (Geotechnical and Geological Engineering, 2020)

Electrostatic Self-assembly Aided Synthesis of CdS/Cs3PW12O40 Hybrids for Photocatalytic Reduction of Cr(VI) - Yunguang Yu; Zhihui Lu; Hong Wei; Xuefang Cao; Kebin Li (Water, Air, & Soil Pollution, 2020)

Genome-wide analysis of laccase genes in moso bamboo highlights PeLAC10 involved in lignin biosynthesis and in response to abiotic stresses - Lichao Li; Kebin Yang; Sining Wang; Yongfeng Lou; Chenglei Zhu; Zhimin Gao (Plant Cell Reports, 2020)

Chronic Copper Exposure Induces Hypospermatogenesis in Mice by Increasing Apoptosis Without Affecting Testosterone Secretion - Hanming Chen; Zhenlong Kang; Na Qiao; Gaoyang Liu; Kebin Huang; Xi Wang; Congying Pang; Qiwen Zeng; Zhaoxin Tang; Ying Li (Biological Trace Element Research, 2020)

Genome-wide identification and expression analysis of brassinosteroid action-related genes during the shoot growth of moso bamboo - Sining Wang; Huayu Sun; Xiurong Xu; Kebin Yang; Hansheng Zhao; Ying Li; Xueping Li; Zimin Gao (Molecular Biology Reports, 2019)

Comparison of the trapping effect and antioxidant enzymatic activities using three different light sources in cockchafers - Yan Gao; Ganghua Li; Kebin Li; Chaoliang Lei; Qiuying Huang (Environmental Science and Pollution Research, 2017)

Co-modified MCM-41 as an effective adsorbent for levofloxacin removal from aqueous solution: optimization of process parameters, isotherm, and thermodynamic studies - Ting Jin; Wenhua Yuan; Yujie Xue; Hong Wei; Chaoying Zhang; Kebin Li (Environmental Science and Pollution Research, 2017)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

QPEEG analysis of the effects of sodium valproate on adult Chinese patients with generalized tonic-clonic seizures - Jiamei Guo; Dan Wang; Min Ren; Bo Xiong; Zengyou Li; Xuefeng Wang; Kebin Zeng (Metabolic Brain Disease, 2014)

Functional identification of the DNA packaging terminase from Pseudomonas aeruginosa phage PaP3 - Xiaodong Shen; Ming Li; Yijun Zeng; Xiaomei Hu; Yinling Tan; Xiancai Rao; Xiaolin Jin; Shu Li; Junmin Zhu; Kebin Zhang; Fuquan Hu (Archives of Virology, 2012)

Rapid purification of photosystem I chlorophyll-binding proteins by differential centrifugation and vertical rotor - Xiaochun Qin; Kebin Wang; Xiaobo Chen; Yuangang Qu; Liangbi Li; Tingyun Kuang (Photosynthesis Research, 2007)